# How do you solve -2x-9y=-25 and -4x-9y=-23?

##### 2 Answers

I found:

#### Explanation:

I would add together the two equations (in columns) after multiplying the first by

Substitute into the first equation:

#### Explanation:

Your system of equations looks like this

#{(-2x-9y = -25), (-4x-9y = -23) :}#

Multiply the first equation by

#-2x-9y = -25| * (-1)#

#2x + 9y = 25#

The system now looks like this

#{(2x+9y = 25), (-4x-9y = -23) :}#

Add the left-hand sides and the right-hand sides of the two equations *seprately* to get

#2x + color(red)(cancel(color(black)(9y))) - 4x - color(red)(cancel(color(black)(9y))) = 25 - 23#

#-2x = 2 implies x= 2/((-2)) = -1#

Take this value of

#-2 * (-1) - 9y = -25#

#2 - 9y = -25#

#-9y = -27 implies y = ((-27))/((-9)) = 3#

The solution set to this system of equations is